2017
DOI: 10.1007/s00702-017-1761-4
|View full text |Cite
|
Sign up to set email alerts
|

Mentally stimulating activities associate with better cognitive performance in Parkinson disease

Abstract: Subjects at risk of dementia benefit from participation in mentally stimulating activities but no prior studies have investigated similar associations in Parkinson’s disease (PD). The aim of this study was to investigate the relationship between times spent engaging in mentally stimulating activities and cognitive functions in PD while accounting for the degree of primary neurodegenerations. PD patients (N=41, 33 males; age 68.5±7.2; Hoehn & Yahr stage 2.6±0.6) completed the Community Health Activities Model P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Regarding work activity, Bohnen et al 25 and Silveira and Portuguez 26 , corroborate the findings of the present study by indicating that involvement in mentally stimulating activities is associated with a better cognitive status among the elderly, including those with PD. The results of the present study indicated that there was an inverse correlation between work activity and SCOPA-COG score, or in other words the higher the category of the profession G(3), the lower the test score.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding work activity, Bohnen et al 25 and Silveira and Portuguez 26 , corroborate the findings of the present study by indicating that involvement in mentally stimulating activities is associated with a better cognitive status among the elderly, including those with PD. The results of the present study indicated that there was an inverse correlation between work activity and SCOPA-COG score, or in other words the higher the category of the profession G(3), the lower the test score.…”
Section: Discussionsupporting
confidence: 89%
“…A recent UK study funded by the Wellcome Trust addressing the effect of dance therapy (ballet) in PD will however aim to include patients with late stage PD in the program (clinicaltrials.gov, NCT04719468). Mentally stimulating activities, such as volunteering, visiting friends, computer use, crafts, attending church or reading, have shown to be associated with better cognitive performance, independently of education, severity of motor disease, nigrostriatal dopaminergic, and cortical cholinergic degeneration [28]. Moreover, social engagement, which has already been associated with decreased risk to develop dementia in the aging population, seems to contribute to individual`s cognitive reserve [29].…”
Section: Can Self-help Management Strategies Help?mentioning
confidence: 99%
“…Future research with larger sample sizes is needed to investigate the relationship between engagement in different types of activity and hearing loss severity. Previous research has indicated that increased time spent on mental activities is associated with improved cognitive functioning [6][7][8]21 and therefore the potential relationship between hearing loss and mental activity engagement warrants further research. In the present study, 6-month post-baseline, the mean number of hours spent on mental activities increased by 1.3 hours for the hearing intervention group and decreased by 1.1 hours for the successful aging group, but the small sample of this pilot study limits any conclusions that can be drawn on the possible benefits of hearing intervention on activity engagement.…”
Section: Discussionmentioning
confidence: 99%